Higher Order Moment of IDXNONCYC on Stock Return PT Nippon Indosari Corpindo Tbk Predictability - Iman Lubis; Syamruddin Syamruddin; Andi Sopandi (YPPP AL-AMSI, 2022)
This study predicts the stock return's of PT Nippon Indosari Tbk with higher order moment of IDXNONCYC. The research method used is time series. Data used are ratios. The tool used is GARCH (1,1). The results are the IDXNONCYC coskewness and cokurtosis lag 1 are significant predicting the stock return’s PT Nippon Indosari Corporindo Tbk. However, IDXNONCYC risk premium lag 1 short fall to predict .